Interleukin-9 in Immunopathology of Trypanosoma cruzi Experimental Infection - Silva, Nadjania Saraiva de Lira; Orikaza, Cristina Mary; Santana, Fabiana Rodrigues de; dos Santos, Luana Aguiar; Salu, Bruno Ramos; Oliva, Maria Luiza Vilela; Sinigaglia, Rita de Cássia; Mortara, Renato Arruda (Frontiers in Cellular and Infection Microbiology, 2021)
Chagas disease is a parasitosis caused by Trypanosoma cruzi, which affects approximately 8 million people worldwide. The balance between pro- and anti-inflammatory cytokines produced during immunological responses contributes to disease prognosis and progression. Parasite tissue persistence can induce chronic inflammatory stimuli, which can cause long-term tissue injury and fibrosis. Chronic Chagas patients exhibit increased levels of interleukin (IL)-9, an important cytokine in the regulation of inflammatory and fibrogenic processes. Data on the role of IL-9 in other pathologies are sometimes contradictory, and few studies have explored this cytokine's influence in Chagas disease pathology. Hence, the aim of this study was to evaluate the role of IL-9 in the progression of T. cruzi infection in vivo and in vitro. In vitro infection demonstrated that IL-9 reduced the number of infected cells and decreased the multiplication of intracellular amastigotes in both C2C12 myoblasts and bone marrow-derived macrophages. In myoblasts, the increased production of nitric oxide (NO) was essential for reduced parasite multiplication, whereas macrophage responses resulted in increased IL-6 and reduced TGF- levels, indicating that parasite growth restriction mechanisms induced by IL-9 were cell-type specific. Experimental infection of BALB/c mice with T. cruzi trypomastigotes of the Y strain implicated a major role of IL-9 during the chronic phase, as increased Th9 and Tc9 cells were detected among splenocytes; higher levels of IL-9 in these cell populations and increased cardiac IL-9 levels were detected compared to those of uninfected mice. Moreover, rIL-9 treatment decreased serum IL-12, IL-6, and IL-10 levels and cardiac TNF- levels, possibly attempting to control the inflammatory response. IL-9 neutralization increased cardiac fibrosis, synthesis of collagens I and III, and mastocyte recruitment in BALB/c heart tissue during the chronic phase. In conclusion, our data showed that IL-9 reduced the invasion and multiplication of T. cruzi in vitro, in both myoblasts and macrophages, favoring disease control through cell-specific mechanisms. In vivo, IL-9 was elevated during experimental chronic infection in BALB/c mice, and this cytokine played a protective role in the immunopathological response during this phase by controlling cardiac fibrosis and proinflammatory cytokine production.